An Overview of Multistate Outbreak Investigations of Salmonella Infections Linked to Fish and Fishery Products, United States – 2012–2021 - Stelios Viazis; Meredith Lindsay; Jennifer Cripe; Spencer Carran; Tiffany Greenlee; Sharon Seelman Federman; Colin Schwensohn; Thai-An Nguyen; Cary Chen Parker (Journal of Food Protection)
Salmonella infections linked to seafood consumption have the potential to cause serious illness, with reported incidence of foodborne illness associated with contaminated seafood increasing in the past decade. While technological advancements over the last decade have made significant progress in the detection, reporting, and determining the source of illness from bacterial pathogens including Salmonella, prevention of these illnesses remains the same, basic sanitation control. We examined data from Salmonella outbreaks linked to fish and fishery products (excluding raw molluscan shellfish) during the period 2012–2021. In that time, there were five confirmed multistate Salmonella outbreaks, including 633 illnesses and 92 hospitalizations associated with fish and fishery products, and four additional multistate outbreaks with 88 illnesses and 12 hospitalizations where fish and fishery products were a suspect vehicle. We summarize common findings and challenges in the traceback investigations related to these outbreaks, particularly considering traceback challenges involving imported seafood, and discuss sanitary practices and regulatory approaches to prevent Salmonella outbreaks linked to fish and fishery products. Some of the most frequent insanitary observations included the safety of the water used in manufacturing food and ice; using water hoses to create overspray that may cross-contaminate food and food contact surfaces in the processing areas; and inadequate cleaning and sanitizing. Environmental contamination (e.g. from bird feces and insects) and improperly sanitized surfaces and cutting tools were also observed in some inspections. Sanitation controls are especially critical for raw ready-to-eat seafood and controls ensuring proper cooking and sanitary conditions and practices after cooking are critical for cooked products. These sanitation controls prevent foodborne outbreaks and recalls, safeguard consumers, and maintain trust in the food supply chain.